2018
DOI: 10.1007/s12079-017-0446-y
|View full text |Cite
|
Sign up to set email alerts
|

A friend in knee: CCN3 may inhibit osteoarthritis progression

Abstract: Osteoarthritis (OA) is a major clinical problem among the ageing population, yet no disease-modifying treatments currently exist. This issue arises, in part, due to the complex processes occurring in the microenvironment of articular cartilage that lead to osteoarthritic changes. Gaining a better understanding of these processes is crucial in developing a viable therapy for OA. A recent report in Journal of Bone Mineral Metabolism by Janune et al. (J Bone Miner Metab 35:582–597, 2016) suggests a novel role for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In addition, CCN3 was previously shown to be induced by glucose starvation [ 37 ]. Another report suggests that recombinant CCN3 ameliorates 1L-1β induced metalloproteinases in cultured chondrocytes by the activation of PI3K/AKT/mTOR pathway [ 38 , 39 ]. Taking these facts into consideration, it is assumed that the observed CCN3 induction may be a protective response against multiple stimuli such as age-related oxidative stress and nutrition shortages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CCN3 was previously shown to be induced by glucose starvation [ 37 ]. Another report suggests that recombinant CCN3 ameliorates 1L-1β induced metalloproteinases in cultured chondrocytes by the activation of PI3K/AKT/mTOR pathway [ 38 , 39 ]. Taking these facts into consideration, it is assumed that the observed CCN3 induction may be a protective response against multiple stimuli such as age-related oxidative stress and nutrition shortages.…”
Section: Discussionmentioning
confidence: 99%
“…CCN3 also modulates the expression of inflammatory molecules in astrocyte . Recently, emerging evidence have indicated that CCN3 may act as a therapeutic target in OA . Mice lacking CCN3 protein have been shown to display osteoarthritic changes in knee articular cartilage .…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, emerging evidence have indicated that CCN3 may act as a therapeutic target in OA. 17 Mice lacking CCN3 protein have been shown to display osteoarthritic changes in knee articular cartilage. 18 CCN3 may inhibit osteoarthritis progression by maintaining the differentiated phenotype of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Since CCN3 was found to direct immature chondrocytes towards articular chondrocytic differentiation (Janune et al 2011), the utility of CCN3 in OA treatment was challenged. In fact, several reports from independent laboratories reported the favorable effects of CCN3 in vitro and in vivo (Janune et al 2017; Peidl 2018; Huang et al 2019). Nevertheless, a recent report indicated that long‐term overexpression of CCN3 in cartilage enhanced age‐related articular cartilage degeneration (Kuwahara et al 2020).…”
Section: Ccn3 In Osteoarthritis and Agingmentioning
confidence: 99%